Terpuruknya Industri Mebel Rotan Cirebon - Oktavianus Marti Nangoy (Bina Nusantara University, 2011)
Cirebon area has long been known as an area that has great potential in the field of furniture and handicraft industry with raw materials of rattan. This region really does not have trees but because of the large rattan hereditary craftsmen at work there, and many there menyebabkan Cirebon rattan industry as a major regional craftsmen and the largest cane producer in Indonesia. But that condition did not last long because it feared since the Minister of Trade Decree No.12 of 2005, contains the opening tap on raw rattan exports, leading, manufacturers prefer to export the raw materials of rattan. Prices of raw materials for furniture and rattan craft also be high because the prices charged for local producers to use the benchmark export price. This ministerial decree on the one side benefit exporters but the industry shut down one side.